Comportamiento de variedades de maiz intercaladas con yuca en las sabanas de Sucre - Mestra M., A. (International Center for Tropical Agriculture, 1990)
The performance of different maize var. (ICA V 109, ICA V 258, SV 901, and Puya (regional)) intercropped with cassava var. Venezolana was assessed in trials conducted in the rural communities of Tokio and Las Cruces (Sucre, Colombia); the influence of intercropping on the yields of both component crops was also determined. Fresh root yields of cassava averaged, in monoculture and in associated cropping, between 12.2 and 16.6 t/ha. The highest yield was obtained in monoculture (23.3 t/ha) and the lowest in associated cropping (10.9 t/ha). Cassava yielded more with improved maize genotypes than with the regional var. Puya. No significant differences were found between the yield obtained in monoculture and that obtained in intercropping with maize ICA V 109; however, significant differences did occur in fresh root yield depending on the maize genotype. (CIAT)